FIPRONIL promotes motor and behavioral changes in honey bees (APIS Mellifera) and affects the development of colonies exposed to sublethal doses - Zaluski, Rodrigo [UNESP]; Kadri, Samir Moura [UNESP]; Alonso, Diego Peres [UNESP]; Martins Ribolla, Paulo Eduardo [UNESP]; Orsi, Ricardo de Oliveira [UNESP] (Wiley-Blackwell, 2015)
Bees play a crucial role in pollination and generate honey and other hive products; therefore, their worldwide decline is cause for concern. New broad-spectrum systemic insecticides such as fipronil can harm bees and their use has been discussed as a potential threat to bees'survival. In the present study, the authors evaluate the in vitro toxicity of fipronil and note behavioral and motor activity changes in Africanized adult Apis mellifera that ingest or come into contact with lethal or sublethal doses of fipronil. The effects of sublethal doses on brood viability, population growth, behavior, and the expression of the defensin 1 gene in adult bees were studied in colonies fed with contaminated sugar syrup (8 mu g fipronil L-1). Fipronil is highly toxic to bees triggering agitation, seizures, tremors, and paralysis. Bees that are exposed to a lethal or sublethal doses showed reduced motor activity. The number of eggs that hatched, the area occupied by worker eggs, and the number of larvae and pupae that developed were reduced, adult bees showed lethargy, and colonies were abandoned when they were exposed to sublethal doses of fipronil. No change was seen in the bees'expression of defensin 1. The authors conclude that fipronil is highly toxic to honey bees and even sublethal doses may negatively affect the development and maintenance of colonies. Environ Toxicol Chem 2015;34:1062-1069. (c) 2015 SETAC
Keywords: Bees; Phenylpyrazoles; Pollinators; Colonies; Fipronil